Acoustic radiation force impulse (ARFI) elastography compared with biopsy for evaluating hepatic fibrosis after liver transplantation: a cross-sectional diagnostic study - Schmillevitch,Joel (2016)
ABSTRACT CONTEXT AND OBJECTIVE: Biopsies are used after liver transplantation to evaluate fibrosis. This study aimed to evaluate the elasticity of transplanted livers by means of a non-invasive examination, acoustic radiation force imaging (ARFI) elastography, correlating the results with the histological analysis. DESIGN AND SETTING: Cross-sectional study in a public university hospital. METHODS: All patients consecutively operated between 2002 and 2010 with an indication for biopsy were evaluated by means of elastography. The radiologist evaluating ARFI and the pathologist doing anatomopathological examinations were blinded to each other's evaluations. RESULTS: During the study period, 33 patients were included. The indication for transplantation was cirrhosis due to hepatitis C in 21 cases (63%). Liver biopsies showed absence of fibrosis (F0) in 10 patients, F1 in 11, F2 in 8 and F3 in 4. There were no cases of F4 (cirrhosis). The difference in ARFI values (degree of fibrosis) was 0.26 (95% confidence interval, CI: 0.07-0.52) between the groups F0-F1 and F2-F4 (P = 0.04). An area under the curve of 0.74 (CI: 0.55-0.94) and a cutoff of 1.29 m/s between the groups resulted in the best relationship between sensitivity and specificity. Sensitivity (0.66; CI: 0.50-0.83) was lower than specificity (0.85; CI: 0.72-0.97). There was no significant difference in ARFI between patients with hepatitis C and those with other diseases. CONCLUSIONS: The values obtained from elastography were not affected by inflammatory reaction or anatomical alterations. A cutoff point of 1.29 m/s separating patients with or without significant fibrosis was identified.